Resource Potential of the Growth of Region's Economy: Tools for Assessment and Implementation - Elena KOLESNICHENKO1; Yana RADYUKOVA1; Larisa BAKULEVSKAYA2; Lyudmila Mikhailovna KORNILOVA3; Evgeniy A. IVANOV3; Maria Leonidovna TOLSTOVA4 (Communications of International Proceedings, 2021)
Purpose: The authors of the article analyze the practical aspects of the priority industries from the point of view of investments, labor attraction and realization of the resource potential and economic growth in one of the regions of Central Russia. Design/Methodology/Approach: Applying advanced panel data techniques, dating from 2005 up to 2019, the researchers focused on the analysis of the key areas of industrial production, the scenarios of their development until 2024 and the ways to attract  investors and labor resources to realize the potential and ensure the growth of the regional economy. As for the methodological basis, the authors applied an integrated approach to study the potential of the available resources. Industry potential can be used effectively only if investments are made in priority industrial areas. Apart from that, it is crucial to increase labor productivity in these industries. Findings: The results showed that the industry of the Central Russian region has sufficient resources for sustainable economic growth. In 2024 it will be possible to achieve development targets in the food industry and mechanical engineering (mainly agricultural engineering). To realize the potential, it is crucial to attract investors, to strengthen human capital and increase labor productivity.  Practical Implications: The authors use a forecasting approach to examine the resource potential for the economic growth of the regional economy and to assess the priority areas of industrial production from the point of view of investments and labor attraction. This approach can be used as a methodological basis to find out which sectors can attract investors and ensure the growth of the regional economy. Originality/Value: To ensure the regional economic growth, modern regional policy should be focused not only on the development of priority sectors, but also on the use of the available resource potential of the key areas of the regional industrial production.
Keywords: Regional Economy; Resource Potential; Capacity Assessment; Regional Economy Development JEL codes: R10; R58.